ExoY, an adenylate cyclase secreted by the Pseudomonas aeruginosa type III system - Yahr, Timothy L. (The National Academy of Sciences, 1998)
The exoenzyme S regulon is a set of coordinately regulated virulence genes of Pseudomonas aeruginosa. Proteins encoded by the regulon include a type III secretion and translocation apparatus, regulators of gene expression, and effector proteins. The effector proteins include two enzymes with ADP-ribosyltransferase activity (ExoS and ExoT) and an acute cytotoxin (ExoU). In this study, we identified ExoY as a fourth effector protein of the regulon. ExoY is homologous to the extracellular adenylate cyclases of Bordetella pertussis (CyaA) and Bacillus anthracis (EF). The homology among the three adenylate cyclases is limited to two short regions, one of which possesses an ATP-binding motif. In assays for adenylate cyclase activity, recombinant ExoY (rExoY) catalyzed the formation of cAMP with a specific activity similar to the basal activity of CyaA. In contrast to CyaA and EF, rExoY activity was not stimulated or activated by calmodulin. A 500-fold stimulation of activity was detected following the addition of a cytosolic extract from Chinese hamster ovary (CHO) cells. These results indicate that a eukaryotic factor, distinct from calmodulin, enhances rExoY catalysis. Site-directed mutagenesis of residues within the putative active site of ExoY abolished adenylate cyclase activity. Infection of CHO cells with ExoY-producing strains of P. aeruginosa resulted in the intracellular accumulation of cAMP. cAMP accumulation within CHO cells depended on an intact type III translocation apparatus, demonstrating that ExoY is directly translocated into the eukaryotic cytosol.